Sistem Pendukung Keputusan Pemilihan Aparatur Desa Terbaik Pada Desa Bendungan Menggunakan Algoritma Profile Matching - Faisal Alqodar; Robby Rizky; Ayu Mira Yunita (Admin Situstika, 2025)
Village officials have the duty to assist the Village Head in carrying out his duties and authority. At the Bendungan Village Office, a decision support system is very necessary to prevent poor performance. Often, village officials neglect and underestimate their duties, so that their performance is not optimal. Until now, there is no decision support system, and there is still a lack of service resources. Therefore, it is necessary to provide a decision support system so that village officials can comply with their duties and achieve maximum performance. The aim of this research is to design and build a Decision Support System to facilitate decision making in selecting the Best Village Apparatus in Bendungan Village in a concrete and objective manner. The method used in building this Decision Support System is, the Profile Matching method or profile matching is a method that is often used as a mechanism in decision making by assuming that there is an ideal predictor variable level that is only met by the subjects studied. The system approach method used is structured design consisting of Flow of Document (FOD), Flow of System (FOS), Context Diagram, Data Flow Diagram (DFD), Entity Relationship Diagram (ERD) and Normalization using MySQL Database and Sublime Tools Text as text editor. The system development method used is the SDLC (Software Development Life Cycle) method. The results of this research show that the decision support system that was built succeeded in simplifying the process of selecting the best village officials, including the stages of criteria, alternatives, weighting, assessment, and ranking reports.